Embryonic and larval development of the mangrove mud clam, Anodontia edentula (Linne, 1758) in the laboratory. - Doyola, Ellen Flor C.
Anodontia edentula samples with shell lenght of approximately 5-7 cm were collected from Brgy. San Roque, Estancia. Six ripe clams (4 females and 2 males) were chosen and induced to spawn. Mature gametes were characterized by the presence of stalked oocytes for the females and motile spermatozoa for the males. Intragonadal injection of 0.3 ml of 4mM serotonin solution was able to induce spawning in both male and female A. edentula. Spawned eggs have a diameter ranging from 80 to 90 um while released sperms were 10 um in lenght., Cleavage zygote occurred 120 min after fertilization. Embryonic development was completed less than 12 h. Fully developed trochophore larvae were observed after 21 h with mean SL of 98.0{ogon}25.6 brevem. Larvae were hatched as straight-hinge veliger within 37 h with mean SL of 127.3-{ogon}19.6 brevem. Pediveliger was reached after 7 days without passing the umbone stage. This last stage in larval development could be attained even if algal feeds of Nannochloropsis sp. were gradually decreased until terminated at the 8th day of the experiment. Pediveliger larvae have mean SL of 148.7-{ogon}33.8 brevem. From the findings of the experiment, it is recommended that further studies should be conducted using high-powered microscope to provide more detailed description of each embryonic and larval stage. Ratio of sperm and egg concentrations needed to have higher survival rate as well as determination of the embryos and larvae survival percentage is encouraged. Moreover, experiments on the mode of nutrition and effects of temperature on the larvae are necessary. Studies on different type of substrate that would trigger settlement among pediveliger larvae are very much recommended.